Family Portrait of Sakinah and Maslahah in the Modern Era (Perspectives of M. Quraish Shihab and Imam Al-Syatibi) - Arief, Hadiyanto; Al Hakim, Muhamad Arief; Fahmi, Moch Dzul (Alhurriyah, 2023)
Conflict in the Islamic family is a problem that continues to occur in some Indonesian society in this modern era. Such as childfree adherents caused by psychological, philosophical and economic factors, pregnancy out of wedlock which has an impact on stress and depression due to shame, interfaith marriage which has implications for the disconnection of inheritance rights in Islamic law and religious choices for children later in life and early marriage which is vulnerable to mental health. Therefore, it is necessary to understand the concepts of sakinah and maslahah to be implemented in family life. This paper aims to provide solutions related to problems in the Islamic family in the modern era with the concept of sakinah M. QuraishShihab which the author then associated with the concept of Maslahah Imam al-Syatibi. The results of this study explain that the concept of sakinah M. QuraishShihab focuses on three aspects, including; aspects of equality, aspects of deliberation and aspects of awareness of meeting needs.Â  While the concept of maslahah Imam Syatibi with the hierarchy of maslahah by seeking the presence of shaleh and pious descendants (Dharuriyyah), seeking trade/business in the family (Hajiyyah) and providing halal food and drinks to the wider community (Tahsiniyyah).Konflik dalam keluarga Islam menjadi permasalahan yang terus terjadi di sebagian masyarakat Indonesia pada era modern ini. Seperti penganut childfree yang disebabkan oleh faktor psikologis, filosofis dan ekonomi, hamil diluar nikah yang berdampak pada stres dan depresi karena timbulnya rasa malu, pernikahan beda agama yang berimplikasi terputusnya hak waris dalam hukum islam dan pilihan agama bagi anak di kemudian hari serta pernikahan dini yang rentan terhadap kesehatan mental. Oleh karenanya perlu memahami konsep sakinah dan maslahah untuk diimplementasikan pada kehidupan keluarga. Tulisan ini bertujuan untuk memberikan solusi terkait problematika dalam keluarga Islam di era modern dengan konsep sakinah M. Quraish Shihab yang kemudian penulis kaitkan dengan Maslahah Imam al-Syatibi. Hasil penelitian ini menjelaskan bahwa konsep sakinah M. Quraish Shihab menitik beratkan pada tiga aspek, diantaranya; aspek kesetaraan, aspek musyawarah dan aspek kesadaran atas pemenuhan kebutuhan.Â  Sedangkan konsep maslahah Imam Syatibi dengan hierarki maslahahnya dengan mengupayakan hadirnya keturunan yang shaleh dan bertakwa (Dharuriyyah), mengusahakan perdagangan/perniagaan dalam keluarga (Hajiyyah) serta memberikan makanan dan minuman yang halal kepada masyarakat luas (Tahsiniyyah).